FORMATION OF LOGICAL OPERATION IN STUDENTS COMPARISONS ON MATERIAL INTERDISCIPLINE TASKS (Pedagogy of Higher and Secondary Education, 2004)
In the article deals with the problems of logical culture of pupils.
Keywords: 3